The Reconstruction of Livelihoods by Survivors of Cyclone Idai in the Chimanimani District of Zimbabwe - Itai Kabonga; Smart Mhembwe; Cowen Dziva (Springer, Cham, 2022)
Cyclone Idai remains the most severe cyclone to befall Zimbabwe to date. The tropical cyclone led to loss of human life and livestock, and massive destruction of property and livelihoods. The magnitude of the cyclone left many survivors displaced, heartbroken, shocked, traumatised and in a quandary regarding how to survive after the disaster. This chapter documents how survivors of the debilitating cyclone Idai are reconstructing their livelihoods in the aftermath of the disaster. The study uses the sustainable livelihoods framework (SLF) to understand the survivors’ utilisation of human agency as they search for livelihoods in the aftermath of cyclone. The utilisation of the SLF allowed the researchers to analyse the assets used by survivors of cyclone Idai in the reconstruction of livelihood strategies and the vulnerability context in which the livelihoods being reconstructed are embedded. For this qualitative study, data were obtained through interviews with survivors of cyclone Idai, observation and review of documents. The study was confined to the Ngangu and Kopa areas of Chimanimani district in the Manicaland Province of Zimbabwe. The study established that survivors of cyclone Idai are pursuing agriculture, alluvial gold panning, informal trading, migration, gambling and prostitution as livelihood strategies. The survivors’ reconstruction of their livelihoods is based on diversifying their livelihood strategies albeit with a myriad of challenges. In light of the challenges, the study recommends resourcing and capitalisation of survivors in areas where they have comparative skills and capacities to ensure the sustainability of post-cyclone Idai livelihood reconstructions.